2001
DOI: 10.1128/mcb.21.18.6198-6209.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Progression and Cell Polarity Require Sphingolipid Biosynthesis in Aspergillus nidulans

Abstract: Sphingolipids are major components of the plasma membrane of eukaryotic cells and were once thought of merely as structural components of the membrane. We have investigated effects of inhibiting sphingolipid biosynthesis, both in germinating spores and growing hyphae of Aspergillus nidulans. In germinating spores, genetic or pharmacological inactivation of inositol phosphorylceramide (IPC) synthase arrests the cell cycle in G 1 and also prevents polarized growth during spore germination. However, inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 45 publications
4
127
0
2
Order By: Relevance
“…In previous studies, these have been difficult to image, but they have been visualized by immunofluorescence (Harris et al, 1994;Araujo-Bazán et al, 2008) and by using a GFP-tropomyosin fusion (Pearson et al, 2004). As reported previously (Harris et al, 1994;Torralba et al, 1998;Cheng et al, 2001), actin was also associated with forming septa (data not shown).…”
Section: Tip Growth Apparatus Of Aspergillusmentioning
confidence: 59%
See 1 more Smart Citation
“…In previous studies, these have been difficult to image, but they have been visualized by immunofluorescence (Harris et al, 1994;Araujo-Bazán et al, 2008) and by using a GFP-tropomyosin fusion (Pearson et al, 2004). As reported previously (Harris et al, 1994;Torralba et al, 1998;Cheng et al, 2001), actin was also associated with forming septa (data not shown).…”
Section: Tip Growth Apparatus Of Aspergillusmentioning
confidence: 59%
“…Actin has been visualized in fixed A. nidulans by immunofluorescence microscopy (Harris et al, 1994(Harris et al, , 1997McGoldrick et al, 1995;Torralba et al, 1998;Cheng et al, 2001), but it has not been imaged in living cells. We consequently constructed a strain expressing a fusion of GFP to the N terminus of actin (A. nidulans contains a single actin gene; Fidel et al, 1988).…”
Section: Localization and Imaging Of Actin And Tropomyosin In Living mentioning
confidence: 99%
“…As shown in Fig. 1A, AbA strongly inhibits the growth of filamentous fungi such as A. oryzae, P. oxalicum, and Acremonium sp., previously reported for the yeast Saccharomyces cerevisiae (W303-1A) and other fungi (7)(8)(9)(10)13). However, growth inhibition by AbA was not observed for any Zygomycetes species such as M. hiemalis, R. microsporus, R. pusillus, and A. corymbifera (Fig.…”
Section: Growth Of Fungi Resistant Tomentioning
confidence: 72%
“…These strains were cultivated in YPG medium (0.5% yeast extract, 0.5% peptone, 0.5% NaCl,1% glucose, pH 6.5) at 28°C for 48 h in 2-liter shaking flasks containing 700 ml of the medium on a reciprocal shaker at 120 rpm (12). For assaying of the growth inhibition by Aureobasidin A (AbA), fungal strains were grown on YPG plates containing 0.1-10 g/ml AbA for 48 h at 28°C (13).…”
Section: Methodsmentioning
confidence: 99%
“…In S. cerevisiae, the deletion of AUR1 induced cell death. Similarly, AUR1 has been identified as an essential gene in A. fumigatus [44,45]. The inactivation of the IPC synthase by gene deletion or by aureobasidin A inhibition leads to ceramide accumulation and defect in cytokinesis in yeast [43,46].…”
Section: Inositolphosphoceramidementioning
confidence: 99%